Design of Incoming and Outgoing Letter Applications Based on Microsoft Access at PT Pos Indonesia (PERSERO) - Tarissa Aulia Dwi Putri; Mohammad Rizal Gaffar (Ebiz Prima Nusa, 2024)
Pos Indonesia is a State-Owned Enterprise (BUMN) that takes part in courier services, logistics, and financial transactions that make PT Pos Indonesia (Persero). The output of the Electronic Service Note (NDE) digital application used today has not met the needs of weekly and monthly reporting, the digital application used has not been grouped based on the needs of weekly and monthly reports at PT Pos Indonesia (Persero). There are still ambiguous names of senders and recipients of letters because the old position account and the new position account are not directly grouped according to the position but still use the name of the old and new account owner due to the transfer of the account owner to the new position. This makes this project a follow-up application of that output to manage Reports. The design and creation of this Microsoft Access-based information system is intended to assist the Administrative Governance Section in managing Incoming Outgoing Mail Reports. The result of this project is the creation of an incoming and outgoing mail database tool that is more effective and efficient in making weekly or monthly reporting that has been tested to users. From the results of the trial, it shows that this tool is considered very good and as needed in making weekly or monthly reporting because it is enough to import existing mail data in the NDE without the need to classify letters one by one because this tool created a database whose job is to classify letters automatically and the use of incoming and outgoing mail queries, Union queries, and crosstab queries whose job is to generate weekly or monthly reports. The results of the trial also showed that there were no obstacles in using these tools.